On the Design of IDEA-128 - Nakahara Jr, Jorge (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2005)
This paper describes five hypothetical realizations of IDEA-128, a 128-bit block cipher, using a 256-bit key, iterating 16.5 rounds, and operating on 32-bit words. These parameters are exactly double the size of the IDEA block cipher’s. These IDEA-128 variants differ only in the multiplicative group structure: Z ∗ 2 32 , Z ∗ 2 32 +1 , GF(2 32 ), Z ∗ 2 32 −1 , or GF(2 32 + 15). All of these designs have weaknesses related to the structure of these multiplicative groups, which lead to decryption failures or cryptanalytic attacks. The overall conclusion is that none of these variants constitute a secure cipher, and thus, help corroborate the design of the MESH ciphers, which operate on 16-bit words and use the same operations of IDEA, but allows text blocks larger than 64 bits, without compromising security.